Pembelajaran Inquiry Untuk Meningkatan Keberanian Berargumentasi Siswa Kelas XI-PBS SMK Negeri 1 Purwokerto - Jazuli, Akhmad; Setiyanto, Eko Budi (AlphaMath : Journal of Mathematics Education, 2020)
This study aims to increase students' courage in proposing arguments in class using inquiry learning using interactive media. The subjects in this study were class XI-PBS which consisted of 34 students. Data collection was carried out in 4 cycles. Data were analyzed using descriptive analysis. The results showed that there was an increase in students 'courage in argumentation which was shown in the form of daring to ask questions, daring to explain, daring to refute friends' answers, daring to correct the mistakes of others. Besides that there is an increase in learning achievement, which is indicated by the average value that increases from cycle 1 to cycle 4.